Red Cell Immunization in Multiply Transfused Thalassaemic Paediatric Patients- A Preliminary Study (Bangladesh Journal of Medical Science, 2026)
Background Multiply transfused thalassaemia patients can develop red cell immunization that can potentially cause haemolytic transfusion reactions and pose problems with compatibility testing for future transfusions. Previous research on red cell immunization in transfusion-dependent thalassaemia patients has not focused on paediatric groups. Objective This study aims to evaluate the prevalence of red cell immunization in transfusion dependent paediatric thalassaemia patients and identify its potential risk factors. Methods Clinical and serological data of transfusion-dependent thalassaemia patients aged 18 years and below were collected retrospectively from the Hospital Laboratory Information System. Results of antibody identification of the alloantibody and/or autoantibody were collected and analysed. Results Of the 32 patients included in our study, 17(53.1%), (11)34.4%, (2)6.3%, (2)6.3%, patients had HbE/β thalassaemia, β-thalassaemia major, alpha thalassaemia, thalassaemia intermedia/homozygous delta beta thalassaemia respectively. Out of 32 patients, five have developed antibodies against RBC antigens, giving rise to the prevalence of red cell immunization at 15.6%, in which 12.5% were alloantibodies and 3.1% were autoantibodies. The alloantibodies detected were anti E, anti-e, anti-c and alloantibody against lowfrequency antigen with an unknown specificity. The autoantibodies were nonspecific autoIgG. No significant association was observed between antibody formation and risk factors such as diagnosis, gender, blood group, age at first transfusion and number of packed cells transfused. Conclusion This study has successfully answered the prevalence of red cell immunization in multiply transfused paediatric thalassaemia. Our data showed prevalence of red cell immunization at 15.6%, in which 12.5% were alloantibodies and 3.1% were autoantibodies. We acknowledged that a bigger sample size with an extended study period is required.BJMS, Vol. 25 No. 01 January’26 Page : 143-149